Application of poly(vinylphenyltrimethylammonium tribromide) resin as an efficient polymeric brominating agent in the α-bromination and α-bromoacetalization of acetophenones. Issue 19 (2nd October 2019) - Han, Bingbing; Zheng, Zubiao; Zheng, Dongcheng; Zhang, Lei; Cui, Peng; Shi, Jianjun; Li, Changjiang
Abstract: The applications of a new supported tribromide reagent based on poly(vinylbenzyltrimethylammonium hydroxide) resin (Amberlite 717) were reported. This supported tribromide resin was used directly in α-bromination and α-bromoacetalization of acetophenones without any other catalyst under mild conditions. The effects of solvents and the amount of the supported tribromide resin on the reactions were investigated. Under the optimal conditions, most of α-bromo and α-bromoacetal of acetophenones were selectively obtained in excellent yields. Graphical Abstract: